PENDEKATAN HUMANISTIK DALAM BIMBINGAN KONSELING DI SEKOLAH UNTUK MENGEMBANGKAN KETERAMPILAN SOSIAL SISWA - Farida Agus Setiawati (Paradigma, 2009)
Violence, angange in a gang flight, dispute, affray and another negative behaviour many baseds on less on ability to build connection positively with another person. Ability to connected positively this called Social Skill. Social skill was ability that got individual by process learning that used to relate to the environment correctly and appropriatety. Various ability related to social skills are self control, caring with other, affiliation, conflict resolution, agreement, independence and good manner. This social skill is base on skill for live or personal skill. Study of social skill is less developed at the school. Manner of study at the school more oriented to develop academic ability likes mathematics, science and language. Potential development and Ability personal student not peculiarly putted into in subject. Study of social skill is not peculiarly putted into in some lesson. This ability development is inserted in so many existing subject and Counselling guidance activity. During the time, Still many BK's teacher that use behaviorisme approach because the activity more in supervise or Maintaineding school rule. In Permendiknas no 27/2008 explained about task context konselor aim to develop potential and independence conseli. Efforts to develop potential and independence conseli this is correcter done with approach humanistik Humanistic approach correctly used to develop student social skill. Various method that used in this approach is open education, confluent education and cooperative learning. This method can used in carry out BK activity program. BK teacher can do it self in counselling guidance activity or cooperating with other teacher in certain subject.Keywords: Social Skill Development, Guidance and Counseling, Humanistic Approach